Modelling of microwave assisted hot-air drying and microstructural study of oilseeds - Hemis, Mohamed; Choudhary, Ruplal; Becerra-Mora, Nathalie; Kohli, Punit; Raghavan, Vijaya (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: A modelling study was performed to solve the heat and mass transfer problems between grain and the ambient air encountered during drying by microwave assisted hot-air dryer, under low microwave (MW) density of 0.2 W/g. Canola (Brassica napus), soybean (Glycine max) and corn (Zea mays) seeds were chosen due to their inherent high oil content. Scanning electron microscopy (SEM) was used to study the effect of drying conditions on the structural characteristics of these oilseeds. A mathematical model was adapted to simulate drying of one seed of canola, soybean and corn. The process of water transfer was modelled based on the effect of vapour pressure on the water molecules inside the seed. It was observed that when the difference between the vapour pressure inside the grain and the surrounding air was higher than, the drying rate increased which led to cracks in the grain. Results showed that the drying rate decreased when the temperature of air inside the cavity of the microwave increased for all the oilseeds studied, because of the reduced differential vapour pressure between the grain and the ambient air. On the other hand, the drying rate increased if the temperature of the inlet air was reduced because the difference between the two pressures increased. It was concluded that by controlling the ambient air, the grains could be protected against popping and cracking because of lower vapour pressure differential during MW assisted hot-air drying.Keywords: mathematical modelling, oilseeds, MW assisted drying, drying rate, SEM imagesDOI: 10.3965/j.ijabe.20160906.2442Citation: Hemis M, Choudhary R, Becerra-Mora N, Kohli P, Raghavan V. Modelling of microwave assisted hot-air drying and microstructural study of oilseeds. Int J Agric & Biol Eng, 2016; 9(6): 167-177.